Design of solar powered light for remote country with poor lighting / Muhammad Imran Roslan and Najibah Ab Latif - Ab Latif, Muhammad Imran; Roslan, Najibah (School of Mechanical Engineering, 2022)
A Solar panel is a panel that uses renewable resources to create energy that helps a lot of people by providing electricity. Solar panel utilisation is a very practical way to produce electricity for many applications. Off-grid living means living in a location that is not serviced by the main electric conventional source of electricity energy, people need to pay high-cost fees for installation but not using this idea. This idea is used to fabricate the prototype of solar powered light for remote countries with poor lighting. The fabrication process involves the resistor, bulb, solar panel, seal, water bottle, and aluminum sheet. Assembly processes have been done and connected to the power source. In conclusion, it is not too late for us to convert from using coal power to solar power by introducing this product. This product can be improvised by professional help and it also helps earth from global warming by reducing the emission of coal power plants or any type of power plant that exists.